System design for inventory management of SMEs in the food industry - Carreño Dueñas, Diego Andrés (2019)
This paper provides a proposal designed to improve the inventory management system of SMEs, especially those in the candy production and sales sector. The objective of the study is to increase productivity in terms of management and control of inventories; therefore, the methodology consists of carrying out a bibliographic review about the context and challenges presented by SMEs related to the application of ICTs. Then, the diagnosis of the company under study will make it possible to calculate the forecast based on the most accurate procedure identified in the previous phase. In conclusion, the aim is to apply an inventory control system using software designed specifically for this company, which will use QR codes for data supply and updating in real time.